FISHERY POTENTIAL ALONG THE INDIAN COASTAL WATERS BETWEEN PORBANDAR AND RATNAGIRI - GAJBHIYE, S. N.; MEHTA, PRATIK; MUSTAFA, S.; NAIR, VIJAYALAKSHMI R. (Journal of Indian Fisheries Association, 2015)
As part of the ongoing marine pollution monitoring programme the coastal stretch between Porbandar and Ratnagiri was considered to assess the fishery potential. Regular experimental trawling was done off Porbandar, Veraval, Diu, Hazira, Daman, Bassein, Bombay, Murud and Ratnagiri at a depth range of 5-25 m during 1988 to 1992. The catch rate varied from 1.2 to 225 kglh (av.20 3 kg/h). Zonewise maximum catch (av.56.8 kg/h) was observed off Ratnagiri followed by off Porbandar (av.30.1 kg/h), off Bombay (av.23.9 kg/h) and off Murud (av.l9.8 kg/h). The area between Hazira and Daman was poor in fish catch. In general, the catch rate showed a fluctuating trend during the period of observation. Among the hundred species identified from the collections the most common species were Coilia dussumieri, Johnius glaucus, Scoliodon lati,caudus, Lepturacanthus savala, Harpadon nehereus, Sardinella longiceps, Pampus sp. and Congresox sp. The community structure and species assemblage at different zones are discussed in detail.